2020
DOI: 10.1002/jez.2428
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of Cl transport in fishes: New insights and their evolutionary context

Abstract: With remarkably few exceptions, aquatic vertebrates maintain internal Cl− homeostasis despite strong and sometimes fluctuating Cl− concentration gradients between extracellular fluids and external environments. In this “Perspective,” we discuss recent advances in the understanding of epithelial Cl− transport at the molecular level within key osmoregulatory organs in fishes. New insights into mechanisms for epithelial Cl− transport in basal lineages are highlighted to provide an evolutionary context. We describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…With NKCC2 ruled out by the lack of bumetanide sensitivity, any further speculation about the mechanisms facilitating the residual I sc that is NCCb-independent ( i.e., insensitive to indapamide) is beyond the scope of this investigation. Further studies are required to elucidate whether the NKCC2/NCC-independent mechanisms of Cl − absorption, which have been shown in the teleost intestine 28 , are also present in lampreys. It is also possible that indapamide simply did not fully inhibit all NCCb activity, even at the highest tested doses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With NKCC2 ruled out by the lack of bumetanide sensitivity, any further speculation about the mechanisms facilitating the residual I sc that is NCCb-independent ( i.e., insensitive to indapamide) is beyond the scope of this investigation. Further studies are required to elucidate whether the NKCC2/NCC-independent mechanisms of Cl − absorption, which have been shown in the teleost intestine 28 , are also present in lampreys. It is also possible that indapamide simply did not fully inhibit all NCCb activity, even at the highest tested doses.…”
Section: Discussionmentioning
confidence: 99%
“…Although these underlying mechanisms for intestinal SW osmoregulation have been elucidated in teleost fishes, whether such molecular mechanisms are present in the lamprey intestine was unknown prior to the present study 28 . Thus, we aimed to functionally characterize the putative molecular pathway for intestinal ion absorption during SW osmoregulation in the sea lamprey ( Petromyzon marinus ).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Claudin 10 paralogs; Section 5), basolateral NKCC, apical CFTR and basolateral NKA, which energises the system (Figure 3). Increased expression of NKCC (Blondeau‐Bidet et al, 2019; Hiroi & McCormick, 2007; Hiroi et al, 2005; Inokuchi et al, 2017; Nilsen et al, 2007; Tipsmark et al, 2004; Tipsmark, Baltzegar, et al, 2008; Tipsmark, Luckenbach, et al, 2008; Wilson et al, 2007) and CFTR (Hiroi et al, 2005; Inokuchi et al, 2017; Marshall et al, 2018; McCormick et al, 2003; Nilsen et al, 2007; Wilson et al, 2007) has been observed in numerous euryhaline fish species in response to SW acclimation and these proteins are believed to coordinate Cl − secretion by SW ionocytes (Shaughnessy & Breves, 2021). Basolateral NKCC transports Cl − from the blood into the cytosol of SW ionocytes, energised by the Na + gradient established by NKA, and apical CFTR facilitates the movement of Cl − into SW down its electrochemical gradient.…”
Section: Ion Regulation In Seawatermentioning
confidence: 99%